2003
DOI: 10.1093/humrep/deg274
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between meiotic spindle location with regard to the polar body position and oocyte developmental potential after ICSI

Abstract: BACKGROUND:The recent development of a computer-assisted polarization microscopy system (Polscope) with which the meiotic spindle can be visualized in living oocytes on the basis of its birefringence permits analysis of the meiotic spindles of oocytes subjected to ICSI. Previous studies have shown that the meiotic spindle is not always aligned with the ®rst polar body (PB) in metaphase II human oocytes prepared for ICSI. In the present study, the relationship between the degree of meiotic spindle deviation fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
105
4
14

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(132 citation statements)
references
References 11 publications
(16 reference statements)
9
105
4
14
Order By: Relevance
“…Rienzi et al found, however, that in case of normal fertilization the cleavage potential of embryos developing from such oocytes was not impaired (13).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Rienzi et al found, however, that in case of normal fertilization the cleavage potential of embryos developing from such oocytes was not impaired (13).…”
Section: Discussionmentioning
confidence: 97%
“…Studies have shown that the spindle is not, as had been assumed, always adjacent to the polar body (11,13,22). Generally, the proportion of oocytes in which the spindle is significantly displaced is low and the displacement is not necessarily associated with poor oocyte and embryo development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the meiotic spindle location with regards to polar body position has been studied (6)(7)(8). In clinical practice, instrument calibration and the condition of the oocyte cytoplasm influence sperm injection.…”
Section: Discussionmentioning
confidence: 99%
“…Blake et al reported that injection at the seven or eleven o'clock position in relation to the polar body resulted in the greatest number of high-quality embryos (5). Moreover, a high degree of misalignment between the meiotic spindle and the first polar body results in an increased risk of fertilization abnormalities (6). The injection procedure is an extremely important step in instituting fertilization; however, it is technically difficult to precisely inject a sperm at a desired location during ICSI.…”
Section: Introductionmentioning
confidence: 99%